Analisa Pemberian Asupan Protein Dan Asupan Zinc Pada Balita Stunting - Matrutty, Virginia Madona; KHOERIYAH, SALIS MIFTAHUL; Rosyad, Yafi Sabila; Monika, Rika; kORA, Firmina Theresia; Ratri , Tifany Hayuning (Sahabat Publikasi Kuu, 2023)
Background: Stunting is a chronic malnutrition condition caused by insufficient nutritional intake over a long period of time due to feeding that is not in accordance with nutritional needs. The incidence of stunting is influenced by several factors, one of which is nutritional intake. Providing insufficient nutritional intake can increase the risk of stunting in toddlers. Research Objective: To determine the description of protein intake and zinc intake in toddlers with the incidence of stunting. Research Methods: The study used a cross-sectional design. In this study using the sampling technique Total Sampling with a sample size of 45 mothers who have toddlers with stunting incidence. Data collection using Food Recall and Microtoise questionnaires.Research Results: Based on the results of the study, it was found that almost all toddlers with stunting had insufficient protein consumption while for zinc intake itself all toddlers with stunting had insufficient zinc consumption.